A Positive Psychology Resource for Students? Evaluation of the Effectiveness of the 6 Minutes Diary in a Randomized Control Trial - Lorenz, Timo; Algner, Mona; Binder, Benjamin (Frontiers in Psychology, 2022)
This study investigated the effects of the 6 Minute Diary (6MT), a commercial diary combining several positive psychology interventions, including gratitude, goal-setting, and self-affirmation exercises, on several mental health outcome measures. In a randomized controlled trial, university students (N = 157) were randomly assigned to one of two groups: 6MT (n = 77) and a wait list control group (n = 80). Participants in the intervention group were instructed to follow the instructions of the 6MT for four weeks. Participants in both groups completed measures of perceived stress, positive and negative affect, self-efficacy and resilience at baseline, after two (t1), and four (t2) weeks. We used path-analyses with autoregressive and cross-lagged effects to test our hypotheses of the effects of the 6MT. Participants in the intervention group reported decreased levels of perceived stress and negative affect, as well as increased levels of resilience and self-efficacy compared to the control group. Positive affect was not statistically significantly influenced. The data showed a statistically significant increased levels of self-efficacy and resilience only after four weeks, suggesting that changing these constructs needs more time. The 6-minute diary does not appear to make individuals fundamentally more positive. However, the intervention may have a protective function against negative influences on well-being.